KURIKULUM PENDIDIKAN ISLAM PERSPEKTIF IMAM AHMAD BIN HANBAL - Pahrurroji (Fakultas Tarbiyah Institut Ilmu Al-Qur'an (IIQ) Jakarta, Indonesia, 2024)
This research examines the Islamic education curriculum from the perspective of Imam Ahmad bin Hanbal. Against the background of the dualistic nature of education in Indonesia, this research aims to explore and explain the concepts of Islamic education that have been put forward by Imam Ahmad bin Hanbal. This research uses a qualitative method with a descriptive-analytical approach to the works of Imam Ahmad bin Hanbal as well as a study of related literature, such as